Micro/nanosystems and biomaterials for controlled delivery of antimicrobial and anti-biofilm agents. (1st December 2020) - Bianchera, Annalisa; Buttini, Francesca; Bettini, Ruggero
ABSTRACT: Introduction: Microbial resistance is a severe problem for clinical practice due to misuse of antibiotics that promotes the development of surviving strategies by bacteria and fungi. Microbial cells surrounded by a self-produced polymer matrix, defined as biofilms, are inherently more difficult to eradicate. Biofilms endow bacteria with a unique resistance against antibiotics and other anti-microbial agents and play a crucial role in chronic infection. Areas covered: Biofilm-associated antimicrobial resistance in the lung and wounds. Existing inhaled therapies for treatment of biofilm-associated lung infections. Role of pharmaceutical nanotechnologies to fight resistant microbes and biofilms. Expert opinion: The effectiveness of antibiotics has gradually decreased due to the onset of resistance phenomena. The formation of biofilms represents one of the most important steps in the development of resistance to antimicrobial treatment. The most obvious solution for overcoming this criticality would be the discovery of new antibiotics. However, the number of new molecules with antimicrobial activity brought into clinical development has considerably decreased. In the last decades the development of innovative drug delivery systems, in particular those based on nanotechnological platforms, has represented the most effective and economically affordable approach to optimize the use of available antibiotics, improving their effectiveness profile. Abbreviations AZT: Aztreonam; BAT: Biofilm antibiotic tolerance; CF: Cystic Fibrosis; CIP: Ciprofloxacin; CRS: Chronic Rhinosinusitis; DPPG: 1, 2-dipalmytoyl-sn-glycero-3-phosphoglycerol; DSPC: 1, 2-distearoyl-sn-glycero-phosphocholine sodium salt; EPS: extracellular polymeric substance; FEV1: Forced Expiratory Volume in the first second; GSNO: S-nitroso-glutathione; LAE: lauroyl arginate ethyl; MIC: Minimum inhibitory Concentration; NCFB: Non-Cystic Fibrosis Bronchiectasis; NTM: Non-Tuberculous Mycobacteria; NTM-LD: Non-tuberculous mycobacteria Lung Disease PA: Pseudomonas aeruginosa ; pDMAEMA: poly(dimethylaminoethyl methacrylate);pDMAEMA-co-PAA-co-BMA: poly(dimethylaminoethyl methacrylate)-co-propylacrylic acid-co-butyl methacrylate; PEG: polyethylene glycol; PEGDMA: polyethylene glycol dimethacrylate;PCL: Poly-ε-caprolactone; PLA: poly-lactic acid; PLGA: poly-lactic-co-glycolic acid; PVA: poli-vinyl alcohol; SA: Staphylococcus aureus ; TIP: Tobramycin Inhalation Powder; TIS: Tobramycin Inhalation Solution; TPP: Tripolyphosphate